Enhancing Corn Yields on Alluvial Soil Through Dolomitic Lime and Azolla sp. Liquid Organic Fertilizer - Jamilah, Jamilah; Fadil, Alfi Rahmat; Ermawati, Ermawati; Diyanti, Afrirona; Thesiwati, Aslan Sari; Yusnaweti, Yusnaweti (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
These soils are subject to periodic flooding, leading to acidic conditions and low fertility. This study aimed to determine the role of dolomitic lime and Azolla sp. liquid organic fertilizer in enhancing corn yields on alluvial soils. The experiment utilized a completely randomized design (CRD) factorial with two factors. The first factor included three dolomite lime dosage levels: 0, 2, and 4 Mg ha−1. The second factor was levels of Azolla sp. liquid organic fertilizer: 0, 50, and 100 ml L−1. Each treatment was repeated three times, resulting in 27 experimental units. Data were analyzed using ANOVA with the F test, followed by the Least Significant Difference (LSD) test at a 5% significance level. Observations included soil pH, plant height, Leaf Area Index (LAI), weight of 100 kernels, corn dry yield, and liming and fertilization efficiency. The relationship between variables and yield is expressed as: Yield = -10.032 + 1.007 pH + 1.796 LAI + 0.17 weight of 100 kernels; R2 = 74.9%. The highest corn yield was 7.35 Mg ha−1 with a liming efficiency of 30%. Applying 100 ml L−1 of Azolla sp. liquid fertilizer resulted in a yield of 7.23 Mg ha−1 with a fertilization efficiency of 28%.